#TITLE_ALTERNATIVE# - Maharja (NIM 15303068), Carya
ABSTRACT: Composting is a process that transforms domestic organic waste into compost which has similar characteristics with fertilizer. Its process involves bio-degradation of complex organic matter into simpler substances. Communal composting units are very rare in Bandun, in contrast they are proliferating in Cimahi. There are already 12 communal composting units situated in residential areas that are constantly operating, with 6 of them are selected for the purpose of this study (RW 05 Kel. Utama, RW 05. Kel Baros, RW 19 Kel. Cigugur Tengah, RW 13. Kel. Pasirkaliki, RW 16 Kel. Cibabat, and RW 15. Kel Cipageran).Pertinent data are obtained from these sites. The measurement of the physical and chemical characteristics of the compost is intended to reveal the characteristic condition of the produced compost. The results are, then, compared with the compost standard of SNI. The test done to the six samples gives these ranged values; moisture content (percent weight) ranges from 35.17-46.97 percent, dry content (percent weight) ranges from 53.03-64.83 percent, volatile content (percent weight) ranges from 33.15-43.14 percent, ash content ranges from (percent weight) 58-66.85 percent, the dominant particles size are 0.85-2 mm, phosphate ranges from 0.31-1.98 percent, organic carbon ranges from 4.77-5.95 percent, N-NH3 0.37-0.65 percent, organic nitrogen ranges from 0.28-0.65 percent, NTK ranges from 0.94-1.02 percent, C/N ratio ranges from 8.32-19.42, potassium ranges from 19-45.5 percent, Fe ranges from 0.05-0.3 percent, Pb ranges from 0-5 mg/kg, Zn ranges from 5-135 mg/kg, Ni ranges from 0-12.5 mg/kg, and Cu ranges from 0.11-0.87 mg/kg The aim of the benefit-cost analysis (BCA) of the communal composting units is to find whether they are economically profitable or otherwise, regardless of the possible externalities. The methods used in this study are NPV (Net Present Value), B/C R (Benefit/Cost Ratio), and IRR (Internal Rate Revenue). There are 2 scenarios for the calculation, one that integrates the composting activity with the domestic waste transportation system (scenario 1) and the one that separates them (scenario 2). The attained results of the NPVs for the 1st scenario ranges from -65,560,00 to -188,550,00, while for the other available scenario are -131,055,000 to -241,460,000. The B/C Rs for the 1st scenario ranges from -0.312 to -2.578, while for the 2nd scenario ranges from -0.704 to -6.98. The IRR for both scenarios are found unable to be calculated. Generally, the results of compost characterization fulfill the SNI standard. Meanwhile the NPVs and the B/C Rs signifies that the project does no produce direct financial profit, all the same it gives indirect benefits, for instance the economization, and the environmental benefit.